Child Protection in the Kid Influencer Era: Regulatory and Law Enforcement Challenges in Indonesia - Annisa, Febrina; Gustaliza, Resma Bintani; Pratimaratri, Uning; Wulandari, Riska (Jurnal El-Thawalib, 2025)
Advances in information technology and improvements in internet network infrastructure, it is becoming easier for everyone to get and work using information technology. Influencers appear when the methods used in marketing use influencer marketing techniques. Currently, many target marketers use child influencers to target children. Because children are considered unable to determine their own will, the role of various parties is needed to prevent child influencers from being exploited. Using or directing children as influencers compromises children's emotional and physical development. This article uses a normative juridical approach, analyzed qualitatively. According to literature research, Indonesia ratified the UN Convention on the Rights of the Child, as shown by Presidential Decree Number 36 of 1990 concerning Ratification of the Convention on the Rights of the Child, Amendments to the 1945 Constitution, including Article 28B Paragraph (2), and Law -Law Number 23 of 2002 concerning Child Protection. During the implementation of child protection instruments, all relevant parties must prioritize initiatives that protect children from exploitation.